Water quality control handbook - Alley, E. Roberts (Mc Graw-Hill, 2000)
This handbook is intended to provide industrial, governmental, and consulting environmental practitioners a quick reference guide to all major areas of water pollution control. Among the topics discussed are the physical, chemical, and biological characteristics of wastewater; monitoring, sampling, and testing methods; the modeling of the effects of pollutants on the environment; effective management, including the establishment of policies and proper documentation; applicable water pollution regulatory standards; and the theory, design recommendations, and practical suggestions for various water pollution control systems